An Analysis of Syntactical Errors and Mistakes Found in English Oral Presentation - Shally Amna (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2021)
When students present oral English presentation, syntactical errors and mistakes will frequently tend to occur. This research is aimed at analysing the syntactical errors and mistakes found in English oral presentation. The sample taken is the students of Economic Faculty in 2018/2019 who were taking Communication and Presentation in English course. This research used qualitative and descriptive methods. The instruments used are the transcription of the oral presentation and interview. The data are analysed descriptively by using the category of syntactical errors and mistakes by Browns (2007) and Corder (1967). The analysis showed that the most common errors and mistakes are in incomplete unit of a sentence, confusion of using part of speech and wrong use of ‘to be’. The result of the study can be used by the lecturer to see the students’ lack of English competency and specify the teaching materials.